Optimization of plant to animal protein ratio in the post larval diel of Macrobrachium rosenbergii - SARMA, ASHIM; SAHU, N P (The Indian Journal of Animal Sciences, 2014)
Optimization of plant 10 animal protein ratio was studied in the diet of Macrobrachiwn rosenbergii post larvae. Five isonitrogenous (35% CP) experimental diets were prepared by us'ing different proponion of animal protein (AP) and plant protein (PP) levels, VIZ. T1 (100% PP), T2 (7S% PP + 25% AP), T3 (50% PP + 50% AP), T4 (25% PP + 75% AP). T5 (100% AP) and fed 105 treatment groups for 60 days. T2 showed better growth performance (weight gain, 116%; SGR, 1.28; FCR, 2.35 and PER, 1.15). However, growth performance among the groups was not statistically significant (P>0.05).